Response to: Maternal Knowledge and Complementary Feeding Practices as Key Determinants of Stunting Among Children Under Five - Heni Puji Wahyuningsih; Sujiyatini Sujiyatini; Indriana Widya Puspitasari (FORIKES, 2026)
Dear Editor,I would like to express my appreciation for the publication of the article entitled “Pengetahuan Ibu dan Pemberian Makanan Pendamping Air Susu Ibu Sebagai Determinan Utama Kejadian Stunting pada Balita” in the Jurnal Penelitian Kesehatan Suara Forikes [1]. The study offers a valuable contribution to the growing body of evidence on the determinants of stunting, particularly within the context of Kelapa Dua, Kairatu Subdistrict, West Seram Regency. One of the strengths of this research lies in its comprehensive approach to identifying key factors associated with stunting, including maternal education, maternal knowledge, exclusive breastfeeding practices, complementary feeding practices, and household economic status. The use of a cross-sectional design combined with Chi-square statistical analysis provides a solid methodological foundation for examining associations between variables, and the findings demonstrate that four out of the five factors investigated were significantly related to stunting prevalence.Despite these strengths, several methodological limitations warrant further consideration. First, the study does not provide a detailed explanation of the indicators used to assess household economic status, which limits the interpretability and depth of analysis for this variable [2]. Without clear operational definitions—such as income thresholds, asset ownership, or expenditure patterns—the construct of economic status remains ambiguous and may not accurately capture socioeconomic disparities relevant to child nutrition.Second, the study does not incorporate or control for biological and environmental determinants that are known to have direct and substantial effects on stunting. Important factors such as birth weight, maternal nutritional status during pregnancy, history of infectious diseases in children, household sanitation conditions, and access to basic health services were not included in the analysis. By focusing primarily on behavioral and social variables—maternal education, knowledge, and feeding practices—the study overlooks the multidimensional and interrelated nature of stunting, which is widely recognized as the outcome of complex interactions between biological, environmental, and social determinants.To enhance the rigor and comprehensiveness of future research, I recommend adopting a multidimensional analytical framework that integrates biological, environmental, and health service–related factors alongside social and behavioral determinants [3]. Incorporating variables such as birth weight, maternal nutritional status during pregnancy, child morbidity patterns, household sanitation quality, and proximity to health facilities would provide a more holistic understanding of the pathways leading to stunting. Such an approach would better reflect the multifactorial etiology of stunting and support the development of more targeted and contextually relevant intervention strategies.Furthermore, the assessment of complementary feeding practices would benefit from the use of objective indicators aligned with WHO or Ministry of Health standards [4]. These may include measures of energy density, protein and micronutrient content, feeding frequency, dietary diversity, and meal consistency. Employing standardized indicators would strengthen the validity of the findings and allow for more meaningful comparisons across studies and populations.In conclusion, this commentary is offered as a constructive contribution to the ongoing development of high-quality public health research in Indonesia. Strengthening methodological rigor and expanding the analytical scope of stunting research will provide a more robust evidence base to inform policy decisions and programmatic interventions aimed at reducing stunting prevalence nationwide.